Workshop to increase the number of students at Engineering Study Program - Carolina; Amandus Jong Tallo (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2018)
Interest of prospective students toward engineering courses both in public and private universities keep decreasing. Data shows that only 14% of students choose engineering courses. In smaller scale, in one private university, students interest taking the engineering course are only 25% compared to student interest on taking the social courses. Purpose of this research was to conclude the reasons why student’s interest toward engineering courses are low, and to comprise some proven solutions, related theories, in order to help solving the problems. Method used in this research is descriptive quantitative. Data used comes from new student’s quisionaire, and related data with student’s number studying engineering course in Kopertis III and in the internal of ABC University. Data analysis showed that current engineering courses which have more students, are engineering courses with social senses such as Architecture, Regional Planning, and Design Product. Along with the theory of 4 (four) aspecs behind the popularity of a figure, all caused by the current trend of prospective student’s interest towards the social study attractiveness which leads to problem soving, the existence of success’s public figures, and industry branding. Direct workshop between lecturer and prospective students, and doing open house in the university could be strategies to increase the numbers of prospective student who want to take engineering course.